Immersive Virtual Reality in Post-Intensive Care Recovery: A Theory-Informed Narrative Review - Cui, Zhenti; Hou, Xiaojie; Lin, Xiaoxiao; Feng, Yaru; Zhang, Yi (Journal of Contemporary Medical Practice, 2026)
Background: Survivors of critical illness may experience persistent physical, cognitive, and psychological problems collectively described as post-intensive care syndrome (PICS). Immersive virtual reality (VR) has attracted interest as a flexible non-pharmacological medium during and after intensive care, but the clinical meaning of “VR intervention” remains unclear because relaxation, education, psychological therapy, and rehabilitation applications operate through different mechanisms. Objective: To develop a clinically grounded account of how immersive VR might support recovery from critical illness, clarify the mechanisms that connect VR design to PICS-related targets, and identify conditions required for safe nursing and rehabilitation practice. Approach: This theory-informed narrative review integrates foundational PICS literature with relevant empirical reports of head-mounted immersive VR in adult intensive care and post-ICU recovery. Literature was selected for conceptual and clinical relevance rather than comprehensive coverage. No formal screening counts, study-level data extraction, risk-of-bias assessment, or quantitative synthesis were undertaken. Main discussion: VR is better understood as a configurable therapeutic medium than as a single intervention. Sensory modulation and attentional capture may support short-term calm and comfort; presence, explanation, and memory reconstruction may contribute to orientation and psychological processing; and embodiment, feedback, and task structure may promote active rehabilitation. These pathways map onto psychological, cognitive/sleep, and physical PICS domains, but they are moderated by alertness, delirium risk, fatigue, sensory and motor capacity, content, dose, timing, staff support, and technical burden. Existing clinical studies are consistent with feasibility and possible short-term benefit in selected patients, while evidence for prevention or treatment of persistent PICS remains insufficient. Conclusions: Immersive VR should not be presented as an established treatment for PICS. Its value depends on matching a defined therapeutic target with appropriate content, interaction, dose, clinical timing, and supervision. A theory-informed framework can help nurses, therapists, and researchers distinguish low-intensity comfort applications from psychologically or physically demanding interventions and select outcomes that correspond to the proposed mechanism.